Community Service Implementation of IoT Water Quality Monitoring for Hydroponic Farming on Marginal Land - Diah Risqiwati; Agus Eko Minarno; Bashor Fauzan Muthohirin; Ahmad Yuda Pratama; Fahrizal Irfanda Bagaskara; Varis Afdholin; Hanugra Aulia Sidharta; Nova Eka Budiyanta (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2026)
This initiative implemented an integrated smart hydroponic–aquaponic system on marginal land in Bakalan Village, Bululawang District, Malang Regency, to support local food diversification and strengthen household food security. Although the village has strong agricultural potential, local production is still dominated by sugarcane, while vegetable needs are largely supplied from outside the village. To address this issue, the program developed a compact cultivation model that combines fish farming and hydroponic planting, supported by an Internet of Things (IoT)-based water quality monitoring system using ESP32 and wireless communication.The monitored parameters included total dissolved solids (TDS), water temperature, pH, turbidity, and humidity, and the collected data were stored in a local server that could be accessed through smartphones connected to the same network. The implementation results showed that the system was able to monitor water quality in real time and detect abnormal sensor readings, which were automatically recorded for further evaluation. Validated measurements indicated relatively stable operating conditions, with water temperature ranging from 26.8 to 27.1°C, pH from 7.1 to 7.7, ambient humidity from 76.8% to 78.7%, and TDS from 620 to 637 ppm. These findings suggest that the implementation of a smart hydroponic–aquaponic system can improve the productive use of marginal land, support more precise cultivation management, and contribute to community-based food security efforts.